Characteristics and Evolution of Cerebral Aneurysms Among Adults Living With HIV: A Retrospective, Longitudinal Case Series. (5th December 2022) - White, Emily I; Anand, Pria; Cervantes-Arslanian, Anna Marisa
Abstract : Objective: To describe the characteristics and evolution of cerebral aneurysms in a large cohort of adults living with human immunodeficiency virus (ALWH). Background: HIV-associated vasculopathy, which can predispose to cerebral aneurysm development, may result from an inflammatory process whereby HIV viral proteins lead to increased chemoattractant and adhesion particles in the vessel wall. Additionally, adventitial layer inflammation has been shown to be strongly associated with HIV infection and vascular changes that may lead to cerebral aneurysm formation. A recent population-based matched cohort study demonstrated a higher rate of subarachnoid hemorrhage in ALWH. It is important to expand the current understanding of risk factors for aneurysm development and the longitudinal course of patients with HIV-associated vasculopathy to help reduce this source of potential morbidity. Design/Methods: The Clinical Data Warehouse was queried for all adult patients evaluated at Boston Medical Center between January 1, 2000, and October 22, 2021 with a history of HIV and at least one cerebral aneurysm. Charts were reviewed for variables including timing of HIV and aneurysm diagnoses, antiretroviral (ART) duration, additional aneurysm risk factors, development of new aneurysms/growth of existing aneurysms, interventions, and clinical outcomes. Results: A total of 50 patients (52% female) were identified, including 82 cerebral aneurysms. Forty-six percent of patients with a nadir CD4 count less than 200 cells/mm 3 (N = 13) developed new aneurysms or were found to have aneurysm growth over time compared with 29% of patients with a CD4 nadir above 200 cells/mm 3 (N = 21). New aneurysms were found or existing aneurysms grew in 67% of those not on ART at time of aneurysm diagnosis (N = 6), 38% of those with inconsistent ART use (N = 8), and 21% of those with consistent ART (N = 19). Conclusions: Among ALWH, lower CD4 nadir and inconsistent ART use may contribute to aneurysm formation or growth. Further studies are needed to more thoroughly characterize this trend.